O envolvimento paterno no contexto da paralisia cerebral: o que os pais têm a dizer? - Oliveira, Gláudya Ariclênia Bernardo Lindolfo de (2018)
The father's journey has been significantly modified and marked by dynamics, contextualized by sociocultural and historical transformations, which demand revisions of values, behaviors and roles, among which the caregiver and educator can emerge, extrapolating the traditional function of family financial provider. In the context of physical disability, the involvement of a child in chronic pathology refers the family to a re-dimensioning of aspects such as: professional, financial, social and emotional. This dissertation focuses on paternity in the context of Cerebral Palsy (CP) of a child with the objective of understanding paternal involvement in the context of CP in the light of Systemic Theory. The nature of this research is qualitative and involved five parents whose children have a diagnosis of CP. They responded to a semi-structured interview, through a script, which was analyzed according to the Thematic Content Analysis. The understanding of the experience of being and feeling the father of a disabled child was based on the construct Paternal Involvement, according to the dimension of the behavior of the father via interaction, accessibility and responsibility. The empirical categories were two thematic areas: a) the family system and the CP: from the process of building paternity to changes in the system; and b) systemic understanding of parental involvement. The main results showed that: 1) the predominant family configuration was nuclear, with the father, in general, being the main provider and the companion dedicating to the care with the child; 2) the news of the diagnosis was received with surprise, sadness and shock; 3) the child's illness caused changes in the organization of the family routine and in the conjugality of the parents; 4) the parents were involved in the care of the child, from the gestational period, with the exception of one of them; 5) everyone said they were available to meet the needs of the child, basically at times when they are present at home; 6) they pointed to work as an impediment to availability, especially in rehabilitation care, and it was remarkable the lack of involvement of the extended family in their support role; 7) parents were unanimous in claiming changes in their way of being and in the conception of life, which promoted their growth and personal maturation; 8) in the field of care, these parents can be characterized as agents inserted in the treatment, even if the majority do not participate systematically in consultations and rehabilitation sessions, 9) the professionals were generally perceived as people who did not offer sufficient incentives for parental participation in the field of care, since they directed the practices and discourses to the maternal figure; 10) despite the difficulties faced, paternal involvement in this context was evaluated as positive. The systematicity, quality and intensity of involvement varied from a more operative involvement and involvement (with supposed less affective involvement) to a participation with a qualitatively different involvement. It is necessary to revisit discourses and practices of the health team to know the stimulus to paternal participation, empowering the family in the field of care. It is pointed out the need for future research to broaden and deepen the understanding of parental involvement in the context of deficiencies and in the new family configurations, allowing the creation of spaces where these men can be listened and stimulated to express themselves, empowering the family, co-responsible in building bonds.